2020
DOI: 10.1093/ofid/ofaa269
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Seek Diagnostic Testing for SARS-CoV-2 With Home, Drive-through, and Clinic-Based Specimen Collection Locations

Abstract: Background SARS-CoV-2 virus testing for persons with COVID-19 symptoms, and contact tracing for those testing positive, will be critical to successful epidemic control. Willingness of persons experiencing symptoms to seek testing may determine the success of this strategy. Methods A cross-sectional online survey in the United States measured willingness to seek testing if feeling ill under different specimen collection scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 32 publications
1
61
0
Order By: Relevance
“…[18] Further, respondents in the same online study reported high willingness to use home-collection kits to receive COVID-19-related testing for their clinical care (92% reported willingness to use self-collection of saliva and 88% reported willingness to selfcollect a throat swab for clinical care). [12] Willingness to use saliva collection and throat swabs for clinical care in that study did not differ by age groups, race/ethnicity, COVID-19 stigma score, COVID-19 knowledge score, or COVID-19 symptomatology. The consistency in the hypothetical willingness to use these methods for research or clinical care, and the acceptability of their use after using the kits, is notable.…”
Section: Plos Onementioning
confidence: 72%
See 2 more Smart Citations
“…[18] Further, respondents in the same online study reported high willingness to use home-collection kits to receive COVID-19-related testing for their clinical care (92% reported willingness to use self-collection of saliva and 88% reported willingness to selfcollect a throat swab for clinical care). [12] Willingness to use saliva collection and throat swabs for clinical care in that study did not differ by age groups, race/ethnicity, COVID-19 stigma score, COVID-19 knowledge score, or COVID-19 symptomatology. The consistency in the hypothetical willingness to use these methods for research or clinical care, and the acceptability of their use after using the kits, is notable.…”
Section: Plos Onementioning
confidence: 72%
“…The United States is in dire need of options to increase screening for SARS-CoV-2 infection and immune experience, and survey data suggest that people might be more willing to collect specimens at home for research and clinical purposes than to travel into labs or clinics to provide specimens. [12,18] At-home self-collection offers possibilities to reduce the exposure of people in need of screening to others by not requiring travel to test; to reduce the need for PPE for invasive screening tests; to offer options for screening of populations without symptoms who might be unwilling to travel to a clinic for testing. Next steps in this development process include modification to kit instructions and assembly, addition of instructions for shipping, development of video instructions (emphasizing areas of lack of clarity or participant concern), and reassessment of kit usability and performance with another group of participants observed by a telehealth clinician in an intended use environment (e.g., home collection).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although all participants and their close contacts were provided information regarding free COVID-19 testing sites, further data is needed to assess the uptake of testing among household contacts. Moreover, interventions to expand low-barrier, community-based COVID-19 testing including self-test kits, mobile testing, or providing direct support to access existing services [6,40] coupled with surveillance systems to monitor and ensure testing uptake among all household and other close non-household contacts, are needed [9,11,12,17].…”
Section: Discussionmentioning
confidence: 99%
“…2 Having highlighted the importance of self-surveillance and testing, success of these strategies will however be dependent on people's willingness to disclose COVID-19 symptoms and willingness to take the COVID-19 test which are also dependent on several factors such as people's perception of COVID-19 and their acceptability of COVID-19 testing. 3 Fear of the unknown about COVID-19 is another factor that can determine the success of the strategies. With progress of the coronavirus pandemic in Nigeria, false and misleading claims in the media have continued to spread more than the disease itself.…”
Section: Introductionmentioning
confidence: 99%